1997
DOI: 10.1063/1.119958
|View full text |Cite
|
Sign up to set email alerts
|

Growth of amorphous-layer-free microcrystalline silicon on insulating glass substrates by plasma-enhanced chemical vapor deposition

Abstract: Using a triode plasma-enhanced chemical vapor deposition (PECVD) system and high H2 dilution of SiH4 (down to a SiH4/H2 gas flow ratio of 0.33/99), amorphous-layer-free μc-Si:H has been successfully grown on insulating glass substrates in the continuous PECVD growth mode. It is demonstrated that an ultrathin layer of such μc-Si:H can serve as a seed layer to facilitate an epitaxial-like growth of μc-Si:H (seeded growth).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…When mc-Si:H thin films are deposited at low temperature either by PECVD or HWCVD, an amorphous incubation layer is formed in the initial stage of the film growth on a glass substrate, until the microcrystalline structure sets in [6,7]. Since this amorphous incubation layer is harmful to the electric properties, intensive researches have been conducted to reduce or eliminate such an amorphous incubation layer in the initial growth stage [8][9][10]. Heya et al [9] suggested a two-step deposition method, where an amorphous incubation layer could be eliminated by changing hydrogen dilution during deposition.…”
Section: Introductionmentioning
confidence: 99%
“…When mc-Si:H thin films are deposited at low temperature either by PECVD or HWCVD, an amorphous incubation layer is formed in the initial stage of the film growth on a glass substrate, until the microcrystalline structure sets in [6,7]. Since this amorphous incubation layer is harmful to the electric properties, intensive researches have been conducted to reduce or eliminate such an amorphous incubation layer in the initial growth stage [8][9][10]. Heya et al [9] suggested a two-step deposition method, where an amorphous incubation layer could be eliminated by changing hydrogen dilution during deposition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that H based ions etch away weak/strained Si-Si bonds to prevent a-Si formation. [18][19][20] Electrode Spacing and Pressure The incident ion is implanted into the subsurface. Case C: Extra energy of an ion enhances the surface diffusion, which allows the ion or other surface species to immigrate with a larger distance before it gets stuck to a surface site or stopped by following incoming species.…”
Section: D104mentioning
confidence: 99%
“…Normally, the formation of the amorphous incubation layer in the low-temperature process mainly comes from the ion bombardment to the growing surface. To reduce or eliminate the amorphous incubation layer, some proposals were made such as using a triode configuration of CCP [25], two-step growth [26] while they would make the deposition system more complicated or prolong the preparation duration. Different from the conventional CCP sources, as a relatively new plasma source, inductively coupled plasma (ICP) shows some advantages in crystalline silicon film deposition because of the low plasma potential, low electron temperature, high electron density ($10 12 cm À3 at 10 mTorr), spatial confinement of discharge and the simplicity of the configuration [27][28][29].…”
Section: Introductionmentioning
confidence: 99%